Fenomena Integrasi Ilmu di Perguruan Tinggi Keagamaan Islam Negeri: Analisis Terhadap Konsep Unity of Sciences di UIN Walisongo Semarang - Hendri Hermawan Adinugraha, Ema Hidayanti, Agus Riyadi (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2018)
The purpose of this study is to describe the historicity of the Islamization of Knowlegde (IoK) movement, and to explain the realization of ​​IoK idea in the sphere of State Islamic Religious College (PTKIN), especially the analysis of the unity of sciences concept at Walisongo State Islamic University of Semarang. This research uses qualitative method with descriptive analysis approach. The results showed that the idea of IoK in Indonesian context was transformed into the domain of the Islamic Religious College which became the central development of Islamic science in the hope of accelerating the ideals of IoK in Indonesia. This change has consequences for every Islamic Higher Education both State and Private especially Walisongo State Islamic University of Semarang, in order to develop the philosophical paradigm of developing sciences integration. This gave birth to various paradigms that could ultimately enrich the achievement of Unity of Sciences (Wahdah al-Ulum) at Walisongo State Islamic University through his Panca Kamil, namely virtuous noble character, insightful unity of science, achievement in academic, career professionally and community services.